The Lotus japonicus NPF3.1 Is a Nodule-Induced Gene That Plays a Positive Role in Nodule Functioning - Vittozzi, Ylenia; Nadzieja, Marcin; Rogato, Alessandra; Radutoiu, Simona; Valkov, Vladimir Totev; Chiurazzi, Maurizio (Frontiers in Plant Science, 2021)
Nitrogen fixing nodules are new organs formed on legume roots as a result of the beneficial interaction with the soil bacteria, rhizobia. Proteins of the nitrate transporter 1/peptide transporter family (NPF) are largely represented in the sub-category of nodule induced transporters identified in mature nodules. The role of nitrate as a signal/nutrient regulating nodule functioning has been recently highlighted in literature and NPFs may play a central role both in the permissive and inhibitory pathways controlling N2-fixation efficiency. Here we present the characterization of the Lotus japonicus LjNPF3.1 gene. LjNPF3.1 is upregulated in mature nodules. Promoter studies show transcriptional activation confined to the cortical region of both roots and nodules. Under symbiotic conditions Ljnpf3.1 knock out mutants display reduced shoot development and anthocyanin accumulation as a result of nutrient deprivation. Altogether, LjNPF3.1 plays a role in maximazing beneficial outcome of the root nodule symbiosis.